Pengaruh Pengungkapan Emisi Karbon, Kinerja Perusahaan, Eco-Efficciency terhadap Nilai Perusahaan Dimoderasi Kinerja Lingkungan - Dian Marlina; Vinola Herawaty (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this researcher is to test and analyze the effect of carbon emissions, Company performance, eco-efficiency on the value of enterprise moderated environmental performance. This research uses companies in the consumer non-cyclic and basic materials sectors listed on the Indonesia Stock Exchange from 2021 to 2023. There are 42 companies that fit the criteria using the purposive sampling method. Analysis of data used by multiple regression analysis Collection of data from financial statements, annual reports and sustainability reports from individual companies. The results of this study show that the disclosure of carbon emissions negatively affects the value of the Company. Corporate performance and eco-efficiency have a positive effect on corporate value. Environmental performance is unable to moderate the effect of carbon emissions disclosure and eco-efficiency on corporate value. Environmental performance can moderate the effect that corporate performance has on corporate value.